Black Sunday - Harris, Thomas (New York : G. P. Putnam's Sons, 1975)
"The gripping race-against-time debut thriller from the internationally bestselling author of The Silence of the Lambs. Vietnam veteran Michael Lander wants the country that made him suffer to suffer in return. Al-Fatah operative Dahlia Iyad wants to help him turn his bold plan into devastating reality. David Kabakov, Mossad's most dedicated soldier, is determined to uncover the plot before it's too late. All he and the FBI know is that it will be apocalyptic. They don't know about the 1,200 pounds of explosives on their way to the states. The largest, deadliest bomb on American soil. That it will detonate in front of millions at the biggest sporting event of the season. The day of horror is nearly here... Black Sunday."--Provided by publisher
National College of Business and Arts
Keywords: Terrorism -- Fiction; Suspense fiction